Radial plant growth - Tonn, Nina; Greb, Thomas (Current biology, 2017)
Summary: One of the extraordinary features of plants is their growth capacity. Depending on the species and the environment, body forms are manifold and, at the same time, constantly reshaped. An important basis of this plastic variation and life-long accumulation of biomass is radial growth. Here, we use this term to describe the ability to grow in girth by the formation of wood, bast and cork. The more technical term for radial growth is secondary growth, which distinguishes the process from primary growth taking place at the tips of stems and roots during plant elongation.